MENINGKATKAN MINAT DAN AKTIVITAS MEMBACA SISWA DENGAN MENGGUNAKAN MEDIA FLIPBOOK KELAS II SD - Yusup Nurdiansah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article is based on the students’ low interest and reading activity in grade II elementary school. Related to this background, the research problems are 1) how is reading interest for the second-grade elementary school students by using flipbooks? and 2) how is the reading activity for the second-grade elementary school students after applying flipbook reading media? The research is designed to increase students’ interest and reading activity by using flipbook media. The research method used was qualitative research with descriptive methods. The sample was 20 students of class II SDN Sayang. Data were collected by observation sheets, field notes, tests, activity assessments, interviews, and documentation. The research results after applying flipbook media to the second-grade students of SDN Sayang were five students’ learning interests and their reading activities improvement. An improvement of reading interest was indicated by the improvement in happy attitude and the number of reading texts. A happy attitude was seen when reading and after the reading process, and the number of reading texts also increased. The improvement in reading activity was indicated by the length, the number of books, and the understanding of the reading text content. The improvement in reading activity was indicated by an improvement in the duration of reading time, the additional books to read, and the understanding of the reading text contents. In conclusion, students’ reading interest and activity could be increased by using flipbook media at least for five lessons. With the five lessons, there was an improvement in students’ interest and consistent reading activities. The recommendation for teachers regarding this research was to use flipbook media to increase students’ interest and activity. The recommendation for the next researcher was to try to increase students’ reading interest and activity in other samples.